Nociceptin/orphanin FQ up‐regulates P2X3 receptors in primary cultures of neonatal rat trigeminal ganglion neurons. (December 2015) - Wang, Yan; Long, Hu; Jian, Fan; Li, Xiaoyu; Yang, Xin; Zhao, Zhihe; Lai, Wenli
Abstract : Recent evidence indicates a nociceptive role of the nociceptin/orphanin FQ–opioid receptor‐like receptor (N/OFQ‐ORL1) system in craniofacial pain; however, the mechanisms of such an effect remain unclear. We investigated whether the action of N/OFQ involves the modulation of P2X3, a pain‐transducing ionotropic receptor. Double‐labeled immunohistochemical staining was used to determine the co‐localization of ORL1 and P2X3 receptors in the trigeminal ganglia (TG) of neonatal Sprague‐Dawley rats. The effect of N/OFQ (at a concentration ranging from 1 pM to 10 nM) on the expression of P2X3 receptors was detected by RT‐PCR, western blotting, and immunocytochemical staining. We found that ORL1 receptors were co‐localized with P2X3 receptors and that the application of N/OFQ could up‐regulate, in a concentration‐dependent manner, the expression of P2X 3 receptor mRNA and P2X3 receptor protein in TG neurons. Immunocytochemical staining also revealed enhanced P2X3 immunoreactivity beneath the neuronal membrane and an increased percentage of P2X3 ‐positive neurons after treatment with N/OFQ. Those effects were completely blocked by a specific ORL1 antagonist, UFP‐101. Our results suggest that the activation of ORL1 receptors by N/OFQ can potentiate P2X3 receptors in primary cultures of neonatal trigeminal neurons, which may be a mechanism for the nociceptive role of N/OFQ in the modulation of craniofacial pain. Our findings may also have implications in treating craniofacial pain.